2017
DOI: 10.5371/hp.2017.29.4.240
|View full text |Cite
|
Sign up to set email alerts
|

Perioperative Comparison of Hip Arthroplasty Using the Direct Anterior Approach with the Posterolateral Approach

Abstract: PurposeThe aim of the current study is to report the advantage and disadvantage of total hip arthroplasty performed in direct anterior approach (DAA) by comparing it to the posterolateral approach (PLA).Materials and MethodsTwenty-five hip arthroplasty done in DAA (12 total hip arthroplasty [THA] and 13 bipolar hemiarthroplasty [BHA]) were compared with the same number done in PLA (13 THA and 12 BHA). Intraoperative assessments including operation time, anesthetic time, bleeding amount were recorded with intra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 26 publications
0
17
0
Order By: Relevance
“…Ten studies [21,22,23,25,27,31,32,36,37,40] (including 5670 participants) reported a comparison of operative time between the two approaches, and the results Fig. 8 Forest plot comparing the incision length of DAA and PLA Fig.…”
Section: Operative Timementioning
confidence: 99%
See 1 more Smart Citation
“…Ten studies [21,22,23,25,27,31,32,36,37,40] (including 5670 participants) reported a comparison of operative time between the two approaches, and the results Fig. 8 Forest plot comparing the incision length of DAA and PLA Fig.…”
Section: Operative Timementioning
confidence: 99%
“…Two studies [25,36] (105 participants) reported a comparison of LLD between the two surgeries. Results showed that LLD after DAA surgery was less than PLA surgery (Fig.…”
Section: Lldmentioning
confidence: 99%
“…They described that DAA does not detach muscle or tendon during the operation, thereby maintaining soft tissue tension which is one of the factors of postoperative dislocation [16]. In this case, we performed THA through a direct anterior approach in order to reduce muscle damage and a risk of artificial joint dislocation [17,18]. At the time of the latest follow-up, the patient had no postoperative complication.…”
Section: Discussionmentioning
confidence: 87%
“…Importantly, the average blood volume loss was 612 mL after the 40th case. Blood loss was dramatically reduced as additional experience was gained 17) .…”
Section: Discussionmentioning
confidence: 99%